Pseudoaneurysm in the Groin (A non - conventional Solution) - Arias, José F; Bogliaccini, Gustavo A; Gastambide, Carmelo (Cirugía del Uruguay, 1981)
A micotic aneurysm in the groin region was successfully treated by arterial autograft. The authors briefly review conventional procedures, their advantages and disadvantages.